ANALYSIS OF LIQUIDITY RATIO FINANCIAL STATEMENTS IN PT. FINANSIA MULTI FINANCE (CREDIT PLUS) TO ASSESS COMPANY PERFORMANCE - Ayu Irma Setiyani (JOSAR (Journal of Students Academic Research), 2018)
This study aims to determine the financial performance of the company PT. Finansia Multi Finance (Credit Plus) in its financial statements for 3 periods from 20152017. The method used in this study is quantitative research. The data used in this study in the form of financial statements for 3 periods from 2015-2017 using a measure of ratio, namely liquidity. PT. Finansia Multi Finance (Credit Plus) in the current ratio shows the percentage, namely in 2015 3910% in 2016 537% and in 2017 567% means that in the current ratio the company is able to pay short-term debt using the company's current assets. Quick ratio shows the percentage of 2015 is 3876%, 2016 is 486% and 2017 is 507% which means that the company's ability to pay short-term debt without inventory increases. Cash ratio shows that in 2015 55%, 2016 92% and 2017 102% percentage obtained shows that the company is unable to pay short-term debt using cash